EIB Working Papers 2020/01 - How can favourable financing improve energy efficiency investments? Evidence from new experimental data (Volume 2020/1) - Ravillard, Pauline (European Investment Bank, 2020)
Financial instruments and technical assistance are effective in increasing investments in energy efficiency.When these favourable conditions are combined, the probability that firms invest in energy efficiency increases by more than a third. These results provide important insights into measures to increase energy efficiency investments, and how to optimally design them, which is key for EU policy-makers and lending institutions.